About the Simo Lazarov`s trilogy: „Light“ (DVD) – „Tale for the Queen of Sheba“ (CD) – „Arachangeles“ (double CD), on the Mony Almalech’s books: „The light in the Old Testament“, „Darkness in the Old Testament“, „Queen, Lilith and the Crow“, „Archangeles" - Becheva, Rositsa (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
About the Simo Lazarov`s music in the trilogy – a philosophical reflection and interpretation of the theme and the text of Mony Almalech’s books, the eternal themes of good and evil, transmitted through the means of electronic music. About the electronic sound – as an object and subject, for its role and dramaturgical potential, for the stylistic features of this music.